Biopolymeric formulations for biocatalysis and biomedical applications - Elnashar, Magdy; Kahil, T. (Hindawi Publishing Corporation, 2014)
Three gel disks formulations prepared using chitosan (Chito) or polyethylenimine (PEI) followed by glutaraldehyde were prepared for biocatalysis and biomedical applications. The carriers have been used to immobilize lactase covalently and it was evaluated in terms of enzyme loading capacity and enzyme kinetics (km and Vmax). The Km of the Chito formulation was almost half that of the PEI formulations, which is favored in industries. On the other hand, the gel disks were evaluated in terms of their swelling kinetics and the gels' morphology using SEM. The mechanism of the three gels' swelling was also studied and it was found to be non-Fickian, where the mechanism of transport depends on both the diffusion and polymer relaxation, which are controlling the overall rate of water uptake. The Chito formulation was 2-5 folds and PEI formulations were 33-62 folds in terms of the swelling rate constant and the diffusion rate, respectively. These results were highly supported by the SEM. This study will help scientists to design the right polymer network for enzymes immobilization as well as control the surface area and the swelling power of the polymers for different applications such as drug delivery systems and tissue engineering.